Asymmetric between Oil Prices and Renewable Energy Consumption in the KSA - Zabat, Lotfi; Sadaoui, Naima; Abid, Mehdi; Abdulrahman, Badreldin Mohamed Ahmed (International Journal of Energy Economics and Policy, 2025)
Examining the impact of oil prices on renewable energy consumption is crucial for supporting the global energy transition, guiding economic and investment decisions, and advancing environmental goals. This research aims to analyze the short-term and long-term connections between fluctuation of oil prices and renewable energy consumption in Kingdom of Saudi Arabia from 1990 to 2020. We utilized nonlinear autoregressive distributed lag (NARDL) models to analyze the impact of positive and negative oil price shocks on renewable energy consumption in KSA. Renewable energy consumption is the dependent variable, while GDP, oil prices, and trade openness are independent variables. The results show that increases in crude oil prices, GDP, and trade openness will boost renewable energy use both in the short term and the long term. Conversely, a decrease in oil prices will reduce renewable energy use in the short run, although this effect will diminish the long term. On a policy note, policymakers should focus on stabilizing renewable energy development through diversification and sustained support, irrespective of oil price fluctuations. Introducing a carbon tax or adjusting fuel subsidies could also encourage a long-term shift toward cleaner energy sources.